Psychiatric rehabilitation patterns in Italy: Results from the Italian Society of Psychosocial Rehabilitation (SIRP) survey - Viganò, Caterina; Ariu, Cassandra; Barbieri, Deborah; Goffredi, Alessia; Ferrara, Luca; Rea, Federico; Barlati, Stefano; Vita, Antonio; , SIRP Survey Group (Frontiers in Psychiatry, 2023)
Introduction Psychiatric rehabilitation can be considered a bidirectional technique, designed to allow patients to achieve their personal target, focusing on the individuals’ strengths and challenges related to these targets and also on the community organizations in which they will live them out. Unfortunately, psychiatric rehabilitation is too often not considered a first line treatment. Moreover, rehabilitation has been confused with a generic and rough practice, consisting of extemporary actions and aimless entertainments designed to fill “the time passing”. Methods The aim of this study was to increase the knowledge and awareness about the state of the art of different systems of management and funding of psychosocial rehabilitation in the Italian “real-world” rehabilitative settings, using a specifically developed questionnaire. Results The data obtained are positive for some aspects of the rehabilitation interventions, in particular for the use of validated tools for the evaluation and revision of projects and for the trend to work on a team, even though the scarcity of evidence-based rehabilitation interventions applied in Italian psychiatric services is less encouraging. Conclusions This survey presents, at least partially, the "real-world" of rehabilitation in Italy so that we can lay the foundations for the definition of an updated, validated and shared network of what is implemented in the context of psychiatric rehabilitation